2020
DOI: 10.20515/otd.796303
|View full text |Cite
|
Sign up to set email alerts
|

Hemorajik Ve İskemik Serebrovasküler Hastalık Tanısı Alan Hastalarda Kan Laktat Düzeyinin Prognoz Üzerine Etkisi

Abstract: Rektal karsinomlarda cerrahi ve sonrasında (adjuvan) kemoradyoterapi ile pelvik nüks oranı oldukça yüksektir. Bu nedenle neoadjuvan kemoradyoterapi (KRT), rektal kanserlerde giderek daha fazla kullanılan bir tedavi protokolüdür. Çalışmamızda rektal kanserlerde tedavi cevabını ortaya koymayı ve hangi klinik-morfolojik prognostik parametrelerin tedavi cevabını tahmin etmede etkili olduğunu belirlemeyi amaçladık. 2016-2019 yılları arasında tanı almış ve neoadjuvan KRT tedavisi görmüş 46 rektal kanserli hasta çalı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In another study, venous blood lactate levels over 2 mmol/L were shown to have a positive correlation with increased 3‐month mortality rates 13 . Yet another study on the effect of blood lactate level on the prognosis of stroke patients showed no correlation for ischemic stroke prognosis but a significantly positive correlation in haemorrhagic stroke prognosis 25 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In another study, venous blood lactate levels over 2 mmol/L were shown to have a positive correlation with increased 3‐month mortality rates 13 . Yet another study on the effect of blood lactate level on the prognosis of stroke patients showed no correlation for ischemic stroke prognosis but a significantly positive correlation in haemorrhagic stroke prognosis 25 .…”
Section: Discussionmentioning
confidence: 97%
“…Rapid advances in the treatment of cerebrovascular diseases have resulted in their shift from the third to the fourth most common cause of death in the United States of America 2,3 . Events related to cerebrovascular diseases represent 25.2% of all deaths in Turkey, making them the second most common cause of death 4 .…”
Section: Introductionmentioning
confidence: 99%